The use of the ALT Flap and Lateral Femoral Cutaneous Nerve for the Reconstruction of Carpal Soft Tissue and Ulnar Nerve Defects: a Case Report - Karonidis, Athanasios; Bouloumpasis, Serafeim; Apostolou, Konstantinos; Tsoutsos, Dimosthenis (Journal of Hand and Microsurgery, 2015)
The anterolateral thigh (ALT) flap has become one of the workhorse flaps, with indications including diverse reconstructive problems. The lateral thigh area is also a useful donor site for nerve grafts. The lateral femoral cutaneous (LFC) nerve can be dissected along with the ALT flap for a substantial length, depending on the requirements of the recipient site. The LFC nerve can be used as a vascularized or non-vascularized nerve graft. The technique offers advantages and it can find clinical applications, satisfying the functional and aesthetic reconstructive requirements of a complex defect. We report the case of a patient who presented with traumatic soft tissue defect of the volar aspect of the wrist and ulnar nerve defect as a complication of a fracture of distal radius. An ALT flap was used to reconstruct the soft tissue defect. The ulnar nerve was resected due to necrosis and the gap was repaired with non-vascularized grafts of the anterior branch of the LFC nerve. The soft tissues were resurfaced successfully without complications. Functional recovery was good for the superficial branch of the ulnar nerve, whereas it was variable for the deep branch of the ulnar nerve. The anterolateral thigh area offers significant advantages as donor site in the reconstruction of complex soft tissue defects being a large source of vascularized skin, fat, fascia, muscle and nerve. This availability allows for single donor site dissection, minimizing the operating time and the associated morbidity.
Keywords: ALT; Lateral Femoral Cutaneous nerve; Nerve graft; Ulnar verve; Microsurgery